(untitled) (Czech Journal of International Relations, 1994)
Reiner Geissler started working on his study entitled Die Sozialstruktur Deutschlands already in 1989, i.e. before the unification of Germany. However, the radical changes in social reality that have taken place since then forced him to change his original concept. In his study, the author provides an analysis of the situation in Germany, which can also be a response to the changes there since 1989. He elaborates on the fundamental phenomena in the development of the social structure in the former Federal Republic of Germany and the former GDR on an empirical basis and indicates the perspectives of social changes in a united Germany. In the center of his attention is the development of material living conditions, the social status of men and women and the family. He relates all this to the development tendencies of the economic and political system. In a comprehensive assessment, the author interprets the basic directions of changes in the social structure in both parts of Germany as modernization.